Establishing child centred practice in a changing world. part B - Frankel, Sam (Emerald Publishing Limited, 2023)
At a time of significant local, national, and international change, in which children are already actively involved, it seems not only right but necessary that we should be seeking to further our knowledge and understanding of what informs and shapes meaningful and effective practice for and with children. Such research has implications across the spaces that children and adults share whether that is at school, at home, in the law courts, in health care through to local, national, and international platforms for social action. Establishing Child Centred Practice in a Changing World, Part B extends the conversation to connect research and practices in a changing world. This edition examines children's voices in relation to research methodologies, in particular co-production, as well as extending conversations around child centred practice from forest schools to the home through to community change initiatives that further understandings of what it means to be a learner and an advocate. Authors from around the world offer a range of perspectives to advance transformational practice in a changing world. Furthering dialogues around the applied relevance of key principles in childhood studies, this diverse edited collection is an important contribution to the fields of education, sociology, childcare and youth policy and practice.
Keywords: Children -- Social conditions.; Education.; Social work with children.; Social Science -- Children's Studies.; Sociology: family & relationships.; elektronické knihy; electronic books